When I need/want to: Normativity, identity, and form in user construals of 'talk-like' tweeting. (December 2016) - Wikström, Peter
Abstract: The focus of this study is on how Twitter users construe talk-like tweeting in metalinguistic utterances. In a material of tweets containing or responding to explicit comparisons of tweeting to talking ( N =520), a broad range of construals are identified, showing Twitter users associating talk-likeness with, e.g., notions of the textual representation of voice, of grammatical (in-)correctness, of accurately reflecting one׳s 'real-life' identity, and of regional or social variation in language use. These associations frequently serve normative functions, enforcing or contesting linguistic and discursive norms in both serious and playful ways. The findings offer a novel perspective on the oft-debated orality of computer-mediated discourse, providing a window on how a process of enregisterment (Agha, 2007 ) is instantiated and how language norms are actively negotiated by participants in everyday online language use on Twitter. Highlights: Metalinguistic activity on Twitter both enforces and challenges traditional norms. Endogenous metalinguistic perspectives emphasize evaluations over form. Twitter users perform and evaluate identity through tweeting about talk. Emic approaches can qualify and enrich theories about orality in CMC.